A Sartrean Typology of Violent Agents - JELER, Ciprian (Studia Universitatis Babeș-Bolyai Philosophia, 2023)
This paper provides a classification of violent agents according to the manner in which they relate to their own goals. By interpreting Jean-Paul Sartre’s discussion of violence in Notebooks for an Ethics, I show that violent agents may be classified into four categories that I call “defenders of the given order,” “instruments of a higher power,” “mineralized subjects” and, finally, “unchained subjects.” I also show how each of these four categories of violent subjects represents a particular manner of, in Sartre’s words, “refusing time” or, in other terms, of refusing to change or to adjust to the situation one finds oneself in.